Urinary extracellular vesicles for RNA extraction: optimization of a protocol devoid of prokaryote contamination. Issue 1 (24th June 2016) - Tataruch‐Weinert, Dorota; Musante, Luca; Kretz, Oliver; Holthofer, Harry
Abstract : Background: Urinary extracellular vesicles (UEVs) represent an ideal platform for biomarker discovery. They carry different types of RNA species, and reported profile discrepancies related to the presence/absence of 18s and 28s rRNA remain controversial. Moreover, sufficient urinary RNA yields and respective quality RNA profiles are still to be fully established. Methods: UEVs were enriched by hydrostatic filtration dialysis, and RNA content was extracted using 7 different commercially available techniques. RNA quantity was assessed using spectrophotometry and fluorometry, whilst RNA quality was determined by capillary electrophoresis. Results: The presence of prokaryotic transcriptome was stressed when cellular RNA, as a control, was spiked into the UEVs samples before RNA extraction. The presence of bacteria in hydrostatic filtration dialysis above 1, 000 kDa molecular weight cut‐off and in crude urine was confirmed with growth media plates. The efficiency in removing urinary bacteria was evaluated by differential centrifugation, filtration (0.22 µm filters) and chemical pretreatment (water purification tablet). For volumes of urine >200 ml, the chemical treatment provides ease of handling without affecting vesicle integrity, protein and RNA profiles. This protocol was selected to enrich RNA with 7 methods, and its respective quality and quantity were assessed. The results were given as follows: (a) Fluorometry gave more repeatability and reproducibility than spectrophotometry to assess the RNA yields, (b) UEVs were enriched with small RNA, (c) Ribosomal RNA peaks were not observed for any RNA extraction method used and (d) RNA yield was higher for column‐based method designed for urinary exosome, whilst the highest relative microRNA presence was obtained using TRIzol method. Conclusion: Our results show that the presence of bacteria can lead to misidentification in the electrophoresis peaks. Fluorometry is more reliable than spectrophotometry. RNA isolation method must be selected in conjunction with appropriate UEV collection procedure. We also suggested that a minimum 250 ml of urine should be processed to gather enough RNA for robust quantification, qualification and downstream analysis.